2021
DOI: 10.21203/rs.3.rs-343388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 mRNA vaccine induced antibody responses and neutralizing antibodies against three SARS-CoV-2 variants

Abstract: As SARS-CoV-2 has been circulating for over a year, dozens of vaccine candidates are under development or in clinical use. The BNT162b2 mRNA COVID-19 vaccine induces spike protein-specific neutralizing antibodies associated with protective immunity. The emergence of the B.1.1.7 and B.1.351 variants has raised concerns of reduced vaccine efficacy and increased re-infection rates. Here we show, that after the second dose, the sera of BNT162b2-vaccinated health care workers (n = 180) effectively neutralize the SA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 21 publications
9
43
0
Order By: Relevance
“…However, this trend was much less pronounced after the second dose and the impact of age was no more statistically significant at day 42. These observations are consistent with recent results obtained by Jalkanen et al who observed that IgG anti-Spike and neutralizing antibodies decreased significantly in the older age group (55–65 years) compared to younger age groups (20–44 years) but neutralizing antibody levels were similar between the two groups three weeks after the second dose [ 26 ]. Furthermore, this negative correlation between age and the magnitude of the antibody response was not observed in our volunteers with a history of previous SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 93%
“…However, this trend was much less pronounced after the second dose and the impact of age was no more statistically significant at day 42. These observations are consistent with recent results obtained by Jalkanen et al who observed that IgG anti-Spike and neutralizing antibodies decreased significantly in the older age group (55–65 years) compared to younger age groups (20–44 years) but neutralizing antibody levels were similar between the two groups three weeks after the second dose [ 26 ]. Furthermore, this negative correlation between age and the magnitude of the antibody response was not observed in our volunteers with a history of previous SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 93%
“…This trend was however much less pronounced after the second dose and the impact of age was no more statistically significant at day 42. These observations are consistent with recent results obtained by Jalkanen et al who observed that IgG anti-Spike and neutralizing antibodies decreased significantly in the older age group (55-65 years) compared to younger age groups (20-44 years) but neutralizing antibody levels were similar between the two groups three weeks after the second dose [25]. Furthermore, this negative correlation between age and the magnitude of the antibody response was not observed in our volunteers with an history of previous SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 93%
“…Emerging variants of SARS-CoV-2 are of clinical concern and vaccine breakthrough infections with SARS-CoV-2 variants in previously fully immunized individuals have been described [14] . These SARS-CoV-2 variants could have a direct impact on the available COVID-19 vaccines, as they can alter the neutralizing activity of vaccine-elicited antibodies resulting in variable loss of efficacy [15] , [16] . However, it is not clear in such cases if it is the lower neutralizing activity of SARS-CoV-2 antibodies, inadequate T-cell responses, or genetic novelty of SARS-CoV-2 variants that caused these infections.…”
Section: Discussionmentioning
confidence: 99%